A new model for the electron pressure nongyrotropy in the outer electron diffusion region. Issue 20 (21st October 2016) - Divin, A.; Semenov, V.; Korovinskiy, D.; Markidis, S.; Deca, J.; Olshevsky, V.; Lapenta, G.
Abstract: We present a new model to describe the electron pressure nongyrotropy inside the electron diffusion region (EDR) in an antiparallel magnetic reconnection scenario. A combination of particle‐in‐cell simulations and analytical estimates is used to identify such a component of the electron pressure tensor in the rotated coordinates, which is nearly invariant along the outflow direction between the X line and the electron remagnetization points in the outer EDR. It is shown that the EDR two‐scale structure (inner and outer parts) is formed due to superposition of the nongyrotropic meandering electron population and gyrotropic electron population with large anisotropy parallel to the magnetic field upstream of the EDR. Inside the inner EDR the influence of the pressure anisotropy can largely be ignored. In the outer EDR, a thin electron layer with electron flow speed exceeding theE ×B drift velocity is supported by large‐momentum flux produced by the electron pressure anisotropy upstream of the EDR. We find that this fast electron exhaust flow with |V e ×B |>|E | is in fact a constituent part of the EDR, a finding which will steer the interpretation of the Magnetospheric Multiscale Mission (MMS) data. Key Points: The outer EDR is created because of upstream electron pressure anisotropy Electron exhaust jet is a part of the electron diffusion region A new model for electron pressure nongyrotropy is created